2010
DOI: 10.1007/s12160-010-9165-9
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder, Cardiovascular, and Metabolic Disease: A Review of the Evidence

Abstract: Background Posttraumatic stress disorder (PTSD) is a significant risk factor for cardiovascular and metabolic disease. Purpose The purpose of the current review is to evaluate the evidence suggesting that PTSD increases cardiovascular and metabolic risk factors, and to identify possible biomarkers and psychosocial characteristics and behavioral variables that are associated with these outcomes. Methods A systematic literature search in the period of 2002–2009 for PTSD, cardiovascular disease, and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
151
4
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(168 citation statements)
references
References 204 publications
(229 reference statements)
8
151
4
5
Order By: Relevance
“…Importantly, although many will experience a traumatic event in their lifetime (70% of the general population), only 7.8% of the US population will go on to develop PTSD in the aftermath of trauma (Keane et al, 2009). PTSD is associated with significant co-morbidities including major depression, substance and alcohol abuse, PD, suicide, reduced life expectancy, as well as disability in daily activities, and increased health care utilization (Dedert et al, 2010;Khoury et al, 2010;Norrholm et al, 2011). Adverse physical health co-morbidities are also common in individuals with PTSD, including obesity, diabetes, cardiovascular disease (Boscarino, 2004;Coughlin, 2011;Heppner et al, 2009).…”
Section: Ptsd and Inflammationmentioning
confidence: 99%
“…Importantly, although many will experience a traumatic event in their lifetime (70% of the general population), only 7.8% of the US population will go on to develop PTSD in the aftermath of trauma (Keane et al, 2009). PTSD is associated with significant co-morbidities including major depression, substance and alcohol abuse, PD, suicide, reduced life expectancy, as well as disability in daily activities, and increased health care utilization (Dedert et al, 2010;Khoury et al, 2010;Norrholm et al, 2011). Adverse physical health co-morbidities are also common in individuals with PTSD, including obesity, diabetes, cardiovascular disease (Boscarino, 2004;Coughlin, 2011;Heppner et al, 2009).…”
Section: Ptsd and Inflammationmentioning
confidence: 99%
“…Yet, PTSD is a significant public health problem with an estimated 8-9% of the population at risk for at least one episode during their lifetime (Hidalgo and Davidson, 2000;Kessler et al, 1995;Yule, 2001). PTSD is associated with multiple adverse outcomes, including psychiatric comorbidity, marital discord, medical illness (Dedert et al, 2010), absenteeism (Alonso et al, 2011), suicide (Kessler, 2000), and an estimated annual productivity loss of approximately $3 billion (Kessler, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the Framingham Coronary Heart Disease study, patients with PTSD were found to have increased Framingham risk scores for CVD (40). To date, there have been six PTSD-CVD prospective studies completed, following participants from 1 to 30 years, which have demonstrated consistent associations between PTSD and CVD after adjusting for demographic, clinical, and psychosocial factors, including depression (15,44,57,58,89,96).There are multiple risk factors (stroke, hypertension, atherosclerosis, and obesity metabolic syndrome) for the development of CVD, and increases in the incidence of these risk factors are often associated with PTSD (1,22,30,51,111 In a 14-year prospective study of more than 1,900 patients, men had an increased risk for both nonfatal myocardial infarction and fatal coronary heart disease with every SD increase in symptom level; similarly, women with five or more PTSD symptoms had over three times the risk of incidence of CVD (57, 58). It is also worth noting that clinically significant PTSD symptoms can be induced by cardiovascular related events, and these individuals are more likely to have recurrent major adverse coronary events (24, 59).…”
mentioning
confidence: 99%
“…There are multiple risk factors (stroke, hypertension, atherosclerosis, and obesity metabolic syndrome) for the development of CVD, and increases in the incidence of these risk factors are often associated with PTSD (1,22,30,51,111 In a 14-year prospective study of more than 1,900 patients, men had an increased risk for both nonfatal myocardial infarction and fatal coronary heart disease with every SD increase in symptom level; similarly, women with five or more PTSD symptoms had over three times the risk of incidence of CVD (57, 58). It is also worth noting that clinically significant PTSD symptoms can be induced by cardiovascular related events, and these individuals are more likely to have recurrent major adverse coronary events (24, 59).…”
mentioning
confidence: 99%